Jonson's Use of the Morality of Vice in Volpone and The Alchemist - Garrett, Christine Jane (My University, 1990)
This thesis is an attempt to demonstrate the ways in which Ben Jonson incorporates some of the qualities of the Morality Vice into the lead characters of Volpone and The Alchemist. While critics have often ignored Jonson's Morality heritage, the similarity between his lead cozeners and the Vice is often striking. Face and Mosca's overwhelming love of the theatre manifests itself in their superior ability to create a drama in which theirscheming partners and ambitious clients expose the faults to which all humanity is prone. Certainly, as it strives to rule the dramatic world, the Vice forms a precarious bond with the audience. Its Morality traits underscore its evil nature and therefore alienate us from the Vice to some degree. However, this figure could imitate humanity and thus invites the audience into an uncomfortable camaraderie which exposes the spectators' own attraction to greed. The first chapter of my thesis examines many of the Vice's central characteristics, such as his love of masks and his ability to create and sustain anarchy. The second chapter examines the shift in power which occurs between Volpone and the true Vice of this play, Mosca.The following chapter focuses on The Alchemist in which Face rises to the Vice's role above his self-deluding companions and their victims. Moreover, this chapter illustrates Face's irresistible theatrical attraction and thus the audience's susceptibility to the visions with which Face baits his clients. The final chapter of my thesis examines the ways in which Jonson alters the Morality tradition in order to make his audience aware of its own moral weakness. The spectator's attraction to the Vice's energy is tempered only by its fear of the evil figure's ability to infiltrate the human realm. Indeed, the relationship between stage and society which the Vice-figure is able to elucidate, becomes an important aspect of Jonson's work. In order to explore this relationship, I have chosen to adapt an audience-response approach to the text. In other words, I visualized how the play would look on stage and noted my reactions to this imaginary performance.
Keywords: English Language and Literature; English Language and Literature